Utility of Follicular Unit Excision Using Nonscalp Donor Hair - Gabel, Steven (Facial Plastic Surgery, 2023)
Nonscalp donor hair harvesting or body hair transplantation offers patients an additional source of donor hair in cases when the scalp does not have an adequate supply for the intended recipient area. The most common applications for nonscalp donor hair are for patients with advanced hair loss or to camouflage scarring from prior hair restoration procedures. For patients with available body hair, the beard is probably the best source followed by the chest and abdomen. Combined, these sources may be able to provide thousands of additional grafts for transplantation. Nonscalp hair donor harvesting is technically challenging and should be performed by those with extensive experience in follicular unit excision surgical techniques.
Keywords: nonscalp donor hair; body hair transplantation; follicular unit excision; linear strip excision; chest hair; beard; torso; nonscalp FUE donor harvesting; caliber